AXILLOFEMORAL FISTULA FOR HEMODIALYSIS ACCESS - Utikal, Petr; Bachleda, Petr; Koecher, Martin; Drac, Petr; Cerna, Marie (Biomedical papers, 2006)
The authors describe the technique of axillo-femoral arteriovenous prosthesis interposition and evaluate their experience with this non-conventional access for hemodialysis.
Keywords: Hemodialysis/Vascular access/Arteriovenous fistula/ePTFE prosthesis/Axillary artery/Femoral vein